Modern methods for assessing the complexity of motor activity and its qualitative performance - Kyzim, P.; Batieieva, N.; Druz, V.; Jegonyan, O. (Slobozhanskyi herald of science and sport, 2020)
Purpose: a single method justification for assessing the complexity of motor activity and quality of its performance. Materials and methods: the carried out researches used empirical materials of dissertation works and research in the field of sports and physical culture, in which various methods for qualitative assessment of performed movements and definition of its complexity category were used. Results: general provisions, which are the basis of motor activity formation, its objectification in subsequent periods of physical development, principles of ranking the complexity of motor activity construction, criteria of constructing the individual algorithm of training and formation of optimal group compatibility in game types of motor activity organization, are established.